2015
DOI: 10.1161/circep.114.001413
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Adverse Outcomes of Percutaneous Left Atrial Appendage Closure for Stroke Prevention in Atrial Fibrillation in the United States

Abstract: Background-Safety data on percutaneous left atrial appendage closure arises from centers with considerable expertise in the procedure or from clinical trial, which might not be reproducible in clinical practice. We sought to estimate the frequency and predictors of adverse outcomes and costs of percutaneous left atrial appendage closure procedure in the US. Methods and Results-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 15 publications
(17 reference statements)
9
33
1
1
Order By: Relevance
“…14 The trial reported a 2.2% rate of early adverse events that included device embolization, arteriovenous fistula, cardiac perforation, pericardial effusion with cardiac tamponade, and major hemorrhage requiring transfusion. Even with the use of broader definitions to include ischemic stroke and other vascular complications, the complication rate is significantly lower than that reported by Badheka et al, 16 4.2% versus 24%, which is at least partly explained by the methodological issues noted. Finally, as noted by the authors, the study is further limited by the inability to identify complication rates for each individual device.…”
Section: Article See P 42contrasting
confidence: 58%
See 1 more Smart Citation
“…14 The trial reported a 2.2% rate of early adverse events that included device embolization, arteriovenous fistula, cardiac perforation, pericardial effusion with cardiac tamponade, and major hemorrhage requiring transfusion. Even with the use of broader definitions to include ischemic stroke and other vascular complications, the complication rate is significantly lower than that reported by Badheka et al, 16 4.2% versus 24%, which is at least partly explained by the methodological issues noted. Finally, as noted by the authors, the study is further limited by the inability to identify complication rates for each individual device.…”
Section: Article See P 42contrasting
confidence: 58%
“…In this issue, Badheka et al 16 report the rates of adverse outcomes associated with percutaneous LAA closure in clinical practice across the United States. Using the Nationwide Inpatient Sample database from 2006 to 2010, the authors report a 24% complication rate, >10-fold higher than the complication rates reported in the PREVAIL trial 14 and submitted to the Food and Drug Administration.…”
Section: Article See P 42mentioning
confidence: 99%
“…Zamykanie LAA może również obniżać ryzyko udaru mózgu u pacjentów z przeciwwskazaniami do OAC [454,455]. Zabieg implantacji może być przyczyną poważnych powikłań [446,[456][457][458], a w analizach baz danych firm ubezpieczeniowych oraz przeglądach systematycznych stwierdzano dużą częstość występowania takich incydentów, co być może wskazuje na pewnego stopnia błąd selektywnego raportowania wyników [446,456]. W niedawnym dużym rejestrze europejskim stwierdzono dużą częstość powodzenia implantacji (98%) z możliwą do zaakceptowania częstością występowania powikłań związanych z zabiegiem, wynoszącą 4% w ciągu 30 dni [459].…”
Section: Leczenie Przeciwpłytkowe Jako Postępowanie Alternatywne W Stunclassified
“…4,5,47 Several strategies have been utilized to estimate the costs related to AF. They include costs associated with anticoagulation and stroke prevention, 48 interventional procedures, 49,50 or pharmacological treatments with regards to rate and rhythm control. 51 Alternatively, costs of AF related to patient setting such as inpatient, outpatient/ambulatory have also been evaluated in the US.…”
Section: Cost Of Afmentioning
confidence: 99%
“…Every unit increase in annual procedural volume was associated with reduced LOS and reduced hospitalization cost. 50 The fundamental work of Haissaguerre showed that AF may be triggered by focal discharges from a pulmonary vein (PV). Eliminating these trigger points via catheter ablation was focused as a reasonable approach to treat AF.…”
Section: Accepted Manuscriptmentioning
confidence: 99%